Structural Behaviour Of Interlocking Hollow Block Concrete Wall With Subjected To Axial and Eccentric Loads - Mohamed, Labeed Ahmed (2008)
The use of structural masonry may result in cheaper and faster construction of structures compared with the conventional approach of framed building construction. In Malaysia the supply of houses by both public and private is still far from meeting the demand especially in low cost housing sector. Hence the search for fast, safe and economical masonry system becomes a necessity to meet the demand for housing in Malaysia. Interlocking block system is promoted, as a new building technique that may result to more economical construction. The main concept of interlocking hollow block system is the elimination of the mortar layers and instead the blocks are interconnected through providing key connection (protrusion and groove). The use of interlocking load bearing hollow blocks in building construction will speed up the construction process as a result of the elimination of mortar layers. Furthermore, due to the self-aligning features of the interlocking hollow blocks, the walls can be assembled much faster by unskilled workers compared to mortar masonry construction.Putra block is an interlocking block system used in the construction of load bearing wall (Waleed et aL(2005)). The structural behavior of the walls constructed using Putra block was presented by Jaafar et al. (2006) and Waleed et al. (2007). The structural behavior of interlocking hollow blocks load bearing wall is not fully explored due limited research on its structural response under the applied load till failure. Moreover, the effect of window opening on the structural response of the interlocking wall especially on the stress distribution in the wall and its failure mechanism are not yet addressed and require special sttention for safe and accurate design of walls. This study presents experimental testing of interlocking hollow block walls having window opening under concentric and eccentric vertical compressive load. The experimental testing focuses on the effect of different layout of the reinforced stiffener around the opening on the structural response of the wall and its failure mechanism. Eight wall panels having dimemion of 1.5 m x 1.6 m (length x height) with a rectangular opening occupying 20% of the wall area were assembled using Putra block. The specimens are differing in the layout of reinforced stiffener around the opening. These wall specimens were subjected to a vertical load of 0 mm, 40 mrn, and 55 rnm eccentricities. The response was investigated in terms of deformation characteristics, strain variation, failure load and failure mechanism. The results indicate that the responses of interlocking hollow block wall with opening are similar to the bonded masonry system. The presence of window opening of an area equal to 20% of the surface area of the wall may reduce the axial efficiency of the interlocking wall up to 50% of the solid wall capacity. Furthermore, the layout of the stiffeners plays a significant effect in the structural response of the interlocking wall and leads to completely different failure mechanism of the wall.